Penerapan Sanksi Pidana Mati Bagi Pelaku Tindak Pidana Pengedar Narkotika Di Wilayah Hukum Kota Tanjung Balai - Sutan Sinomba Parlaungan Harahap; Madiasa Ablisar; Ekaputra Ekaputra; Sunarmi Sunarmi (Iuris Studia: Jurnal Kajian Hukum, 2021)
The provision of the death penalty for narcotics crimes is one of the measures taken by the state to execute drug dealers that could damage generations of the nation, and with Law No. 35 of 2009 on Narcotics can ensnare dealers or drug dealers by giving the harshest punishment that is the death penalty. The issues raised in this study are how to set up criminal sanctions, the application of criminal sanctions in the form of the death penalty, and the consideration of judges in imposing criminal sanctions in the form of the death penalty for the perpetrators of narcotics dealer crimes, especially in the jurisdiction of Tanjung Balai City. To find the answer to the problem, this study used a type of normative legal research that is descriptive analytical, in which this normative legal research uses secondary data as the primary data by using data collection techniques carried out by library reseacrh, as well as data analysis using qualitative data analysis methods.